PENGARUH PEMAHAMAN VISI MISI, KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. SINAR MATAHARI BARU - Shofiyah Rahma; Mariana Natalia Siregar; Mey Ariska Manullang; Kristi Endah Ndilosa Ginting (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
In this research, the target is to analyze the effect of understanding the vision and mission, competence and communication on the performance of employees of PT. New Sunshine separately (partial) to the research. In this study, the material is sourced from primary and secondary data which is then collected into questionnaire data. The number of samples as many as 38 employees. Study testing with multiple linear analysis method. There is a T-count < T-table or l -0.683 < 2.03011 in the partial hypothesis testing and the significant value is 0.200 > 0.05. There is a value of Tcount > Ttable of -1.30 < 2.03011 and a significance size of Tcount of -0.683 < 2.03011 with a significant value of 0.499. Tcount > Ttable -0.683 < 2.03011. Partially, vision and mission, competence and communication have a negative and insignificant impact on employee performance. The adjusted r-square value of 0.123 was obtained from the coefficient of determination test in which 12.9% came from employee performance as the dependent variable which could be explained by variations of the independent variables vision mission, competence and communication. The remaining 87.1% (100% -12.9%) is explained from other variables that are not researched in research.